Pluto's secret : an icy world's tale of discovery - Weitekamp, Margaret A., 1971-; DeVorkin, David H., 1944-; Kidd, Diane (New York : Abrams Books for Young Readers, 2013)
Provides the history of the small, icy world of Pluto from its discovery and naming to its recent reclassification, and explains how scientists organize and class our solar system as they gain new insights into how it works and what types of things exist within it.
"Published in association with the Smithsonian National Air and Space Museum."
Includes bibliographical references (p. 38) and index.
Kirkus Review
Kirkus Review, January 2013
3.6
K-3
Keywords: JUVENILE NONFICTION / General; JUVENILE NONFICTION / Science & Nature / Astronomy; Pluto (Dwarf planet) -- Juvenile literature; Pluto (Dwarf planet); Pluto (Dwarf planet); Picture books for children